STRATEGI ADAPTASI TEKNOLOGI DI ERA HYPER-CONNECTIVITY: MEMBANGUN EKOSISTEM DIGITAL YANG BERKELANJUTAN - Hadid Abdillah Dzulfaqqor; Hudha Syururi; Claffinova Thesar Rafaga; Amnah Amnah (Jurnal Intelek Insan Cendikia, 2025)
Digital Transformation 5.0 marks a new phase of technological acceleration that integrates human-centered connectivity, artificial intelligence, and cyber-physical systems into an interconnected ecosystem. This study aims to examine effective technology adaptation strategies for educational institutions, business organizations, and public sectors operating in the era of hyper-connectivity. The method employed is a literature review based on recent journals, industrial reports, and publications related to digital technology implementation. The findings reveal that successful transformation relies on three core aspects: human resource readiness, sustainable technological integration, and strengthened cybersecurity. Effective adaptation requires a collaborative approach, the utilization of artificial intelligence as a decision-support system, and the development of a digital work culture responsive to rapid changes. This study provides strategic recommendations for institutions to build an inclusive, secure, and sustainable digital ecosystem.